The Family Problems from the Children’s points of View and Relationship with School Bullying– Afield Study on sample of Sixth Grade Students in Lattakia City - قنجراوي فاطمة; أسامة محمد; إيمان عبود (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current research aimed to identify the level of family Problems from the Children’s points of View in Lattakia city, as well as the reality of school bullying among sixth grade students in Lattakia city, and to reveal the relationship between family Problems and school bullying among students, the researcher used the descriptive approach, and to achieve the goal of the research, two tools were built, the first is the family Problems scale consisting of (26) phrases, and the second is the school bullying scale, which consisted of (46) items, and the two tools were applied to a sample composed of (280) students from the sixth grade in the schools of Lattakia city for the academic year 2022/202. The results of the research showed that the level of family Problems from the Children’s points of View in Lattakia city came to a medium degree, and the level of school bullying came to them to a medium degree, and there is a statistically significant and good relationship between family Problems and school bullying among sixth grade students in Lattakia city. In light of the results of the research, several recommendations were made as follows: Promoting the correct and proper family upbringing of children, parents’ embrace of their children, satisfying their psychological and emotional needs, and employing their energies positively, and other studies link both family Problems and school bullying to other variables.